Human Papillomavirus (HPV) Infection in Early Pregnancy: Prevalence and Implications - Deeksha Pandey; Vani Solleti; Gazal Jain; Anwesha Das; Kabekkodu Shama Prasada; Shobha Acharya; Kapaettu Satyamoorthy (Hindawi Limited, 2019)
Introduction. Young women (20-35 years) are at high risk of HPV infection, although the majority of the infections are asymptomatic and are cleared spontaneously by the host immune system. These are also the group of women who are sexually active and are in the population of pregnant women. During pregnancy, the changes in the hormonal milieu and immune response may favor persistence of HPV infection and may aid in transgenerational transmission thereby furthering the cancer risk. In the present study, we determined the prevalence of vaginal HPV infection in early pregnancy and attempted to relate with pregnancy outcome. Material and Methods. Vaginal cytology samples were collected from the condoms used to cover the vaginal sonography probe during a routine first trimester visit to the hospital. All women were followed up throughout pregnancy and childbirth. Maternal and neonatal outcomes were recorded. Results. We found a prevalence of HPV infection around 39.4% in our population. Interestingly all HPV positive women were infected with one or more high risk HPV viruses with an overlap of intermediate and low risk in 43% and 7.3%, respectively. Women with preterm prelabor rupture of membranes (PPROM) showed a statistically higher incidence in HPV positive (7.3%) group as compared to the HPV negative (3.2%) group. Conclusion. The prevalence of genital HPV infection is high during pregnancy (around 40%) and was associated with higher incidence of PPROM.